Epistemologic perspectives of the dialectic and transdisciplinary approaches in nature and socio-humanitarian sciences - Білецький, І. П.; Коннова, Н. О. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
The article is dedicated to analysis of perspectives of the dialectic and transdisciplinary approaches in nature and socio-humanitarian discources or, more concretely, to question of whether it is possible to consider the transdisciplinary approach a modern and logically improved version of the so-called dialectical approach used in philosophy of the well-known dialectic materialism. It is proposed to analyse different interpretations of what dialectic is, what relations it has to key principles of the transdisciplinary philosophy, to follow how they work in different scientific disciplines.